1998
DOI: 10.1046/j.1365-294x.1998.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular resolution of marine turtle stock composition in fishery bycatch: a case study in the Mediterranean

Abstract: Based on an extensive sampling regime from both nesting populations and bycatch, frequency analyses of mitochondrial (mt) DNA control region haplotypes in the Mediterranean were used to assess the genetic structure and stock composition of the loggerhead sea turtle, Caretta caretta, in different marine fisheries. The analyses show the following. (i) In drifting longline fisheries working in Mediterranean pelagic habitats 53-55% of turtles caught originated from the Mediterranean stock; (ii) In bottom-trawl fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
175
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 28 publications
7
175
1
2
Order By: Relevance
“…However, individuals tagged in the Atlantic have been found in the eastern Mediterranean as well, as far as the Sicily Channel (Bolten et al 1992) and the north Ionian Sea (Manzella et al 1988). Genetic studies too have indicated high proportions of Atlantic individuals in the oceanic zone of the Sicily Channel (Laurent et al 1998) as well as their occurrence in the neritic zone of the Tunisian continental shelf (Figure 5), though at a lower proportion (Casale et al 2008b). Current data suggests that Atlantic turtles do not enter the Adriatic or do so in very low numbers (Giovannotti et al 2010;Garofalo et al 2013).…”
Section: Atlantic Loggerheads In the Mediterraneanmentioning
confidence: 99%
See 2 more Smart Citations
“…However, individuals tagged in the Atlantic have been found in the eastern Mediterranean as well, as far as the Sicily Channel (Bolten et al 1992) and the north Ionian Sea (Manzella et al 1988). Genetic studies too have indicated high proportions of Atlantic individuals in the oceanic zone of the Sicily Channel (Laurent et al 1998) as well as their occurrence in the neritic zone of the Tunisian continental shelf (Figure 5), though at a lower proportion (Casale et al 2008b). Current data suggests that Atlantic turtles do not enter the Adriatic or do so in very low numbers (Giovannotti et al 2010;Garofalo et al 2013).…”
Section: Atlantic Loggerheads In the Mediterraneanmentioning
confidence: 99%
“…The modal size of loggerheads found on the Atlantic coast of northern Europe is about 23 cm CCL (20.5 cm straight carapace length, Hays & Marsh 1997; converted according to Bjorndal et al 2000), suggesting that Atlantic turtles enter the Mediterranean at this size or larger. The smallest turtle found in the eastern Mediterranean and carrying an mtDNA haplotype endemic to the western Atlantic was in the size range 30-34 cm CCL (Laurent et al 1998). Genetic markers have shown that Atlantic loggerheads occur in high numbers, especially in the oceanic zone of the westernmost part of the Mediterranean basin, closer to the Strait of Gibraltar, through which they enter from the Atlantic ( Figure 5) (Carreras et al 2006).…”
Section: Atlantic Loggerheads In the Mediterraneanmentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile loggerheads leading a pelagic existence grow at rates of 1-2 inches (2.9-5.4 cm) per year (Bjorndal et al 2003;Snover 2002) over a period as long as 7-12 years ) before moving to more coastal habitats. Recent studies have suggested that not all loggerhead sea turtles follow the model of circumnavigating the North Atlantic Gyre as pelagic juveniles, followed by permanent settlement into benthic environments (Bolten and Witherington 2003;Laurent et al 1998). These studies suggest some turtles may either remain in the pelagic habitat in the North Atlantic longer than hypothesized or move back and forth between pelagic and coastal habitats interchangeably (Witzell 2002).…”
Section: Life History Informationmentioning
confidence: 99%
“…is well established, most surveys have analysed the population structure revealed by mitochondrial DNA (mtDNA) (Encalada et al 1998;Laurent et al 1998;Kaska 2000;Bowen et al 2004;Carreras et al 2006). Nuclear markers such as microsatellites have allowed the identification of conservation and management units, the differences in the migratory behaviour of males and females, and the mating behaviour of several marine turtle species (Crim et al 2002;Bowen et al 2005;Jensen et al 2006).…”
mentioning
confidence: 99%